Collaborative Tourism Study of the “Aromatic Wellness Trip” in Integrating Wellness Tourism and Cultural Tourism by Lokananta and Rumah Atsiri in Solo - Lestari, Dita Ayu; Iskandar, Yeremia; Rahmah, Latifahtur (Journal of Tourism Economics and Policy, 2026)
The post–COVID-19 pandemic growth of wellness tourism has created opportunities for destinations to offer travel experiences that are not only recreation-oriented but also support tourists’ physical health, mental well-being, and spiritual wellness. This study examines the collaborative tourism program “Aromatic Wellness Trip” as an effort to integrate wellness tourism and cultural tourism through cooperation between Lokananta as a historical and music tourism destination, Rumah Atsiri as an essential-oil edu-recreation destination, and Atsiri Jawa as a culture-based wellness destination in the Solo–Tawangmangu area. The research adopts a descriptive qualitative approach, with data collected through a literature review, participant observation, and in-depth interviews with the managers of Lokananta, Rumah Atsiri, and Atsiri Jawa. The findings indicate that the collaborative packages—Day Experience and Cultural Wellness Journey—are able to create a holistic travel experience that combines music-history education, essential-oil exploration, wellness activities, and the internalization of Javanese cultural values. This collaboration contributes to strengthening Solo’s image as a cultural and wellness destination, increasing economic value added for the participating destinations, and preserving historical heritage and local wisdom. Nevertheless, challenges related to program sustainability, human resource capacity, and promotional intensity still require a more structured collaborative management strategy. The findings are expected to serve as a reference for developing sustainable collaborative tourism models in other destinations across Indonesia.